HEMATOLOGICAL PARAMETERS AS PREDICTORS OF SEVERITY IN COMMUNITY-ACQUIRED PNEUMONIA: A CASE-CONTROL STUDY - Dr. Jignasa J. Mansuriya; Dr. Jaimin A. Mansuriya; Mr. Alok Pritam (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Community-Acquired Pneumonia (CAP) continues to represent a substantial public health burden in India, characterized by high rates of severity and associated mortality. Effective, rapid, and cost-efficient risk stratification tools are essential for timely intervention in resource-constrained tertiary care settings. While standard clinical scoring systems, such as the CURB-65, are widely used, their reliance on clinical judgment and potentially delayed laboratory results can hinder early triage. Hematological ratios, particularly the Neutrophil-to-Lymphocyte Ratio (NLR) and the Platelet-to-Lymphocyte Ratio (PLR), offer readily available markers reflecting the interplay between systemic inflammation and the host immune response. Objectives: The primary objective of this study was to evaluate the predictive utility of admission NLR and PLR in identifying Severe Community-Acquired Pneumonia (SCAP), defined by the 2007 Infectious Diseases Society of America/American Thoracic Society (IDSA/ATS) criteria, among adult patients presenting to a North Indian tertiary care center. Methods: A retrospective, single-center case-control study was conducted at the Shri Guru Ram Rai Institute of Medical & Health Sciences, Dehradun, India, utilizing medical records from 01 May 2023 to 30 October 2023. Sixty patients classified as SCAP (Cases: meeting ≥ 1 major or ≥ 3 minor IDSA/ATS criteria) were compared against 120 non-severe CAP patients (Controls). NLR and PLR were calculated from the first Complete Blood Count (CBC) obtained upon admission. Receiver Operating Characteristic (ROC) curve analysis was performed to determine the optimal cut-off values and discriminatory power (Area Under the Curve, AUC). Binary logistic regression was employed to calculate Adjusted Odds Ratios (AORs), controlling for established clinical risk factors, including age and CURB-65 score. Results: SCAP patients exhibited significantly elevated mean NLR (14.5 ± 5.9) and PLR (288.7 ± 110.2) compared to controls (NLR: 5.8 ± 2.1; PLR: 175.3 ± 65.5; P<0.001 for both). ROC analysis identified an optimal NLR cut-off of 8.5 (AUC 0.85, 95% CI 0.79–0.91), demonstrating superior discriminatory ability compared to PLR (AUC 0.78). Multivariate analysis revealed that NLR >8.5 was an independent predictor of SCAP (AOR 4.95, 95% CI 2.15–11.40; P<0.001), retaining statistical significance even after adjustment for the CURB-65 score.